2022
DOI: 10.1371/journal.pcbi.1010607
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of potassium homeostasis: Effect of feedforward and feedback controls

Abstract: Maintaining normal potassium (K+) concentrations in the extra- and intracellular fluid is critical for cell function. K+ homeostasis is achieved by ensuring proper distribution between extra- and intracellular fluid compartments and by matching K+ excretion with intake. The Na+-K+-ATPase pump facilitates K+ uptake into the skeletal muscle, where most K+ is stored. Na+-K+-ATPase activity is stimulated by insulin and aldosterone. The kidneys regulate long term K+ homeostasis by controlling the amount of K+ excre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…(We have previously found that the distal tubule target resulted in similar results to collecting duct reabsorption [39]. )…”
Section: Muscle-kidney Cross Talk Effectsmentioning
confidence: 65%
See 2 more Smart Citations
“…(We have previously found that the distal tubule target resulted in similar results to collecting duct reabsorption [39]. )…”
Section: Muscle-kidney Cross Talk Effectsmentioning
confidence: 65%
“…In our previous study [39], we used our mathematical model to conduct "what-if" simulations of muscle-kidney cross talk under short-term K + loading or depletion. Specifically, we found that in our baseline model (i.e., no muscle-kidney cross talk) after 4 days of K + loading (high K + intake), plasma [K + ] levels started to reach hyperkalemic levels and intracellular [K + ] levels remained high for several days after returning to normal K + intake [39]. When the muscle-kidney cross talk signal was included, model simulations predicted that intracellular [K + ] levels remained within normal range.…”
Section: Results For Predicted Intracellular [Kmentioning
confidence: 99%
See 1 more Smart Citation
“…A whole-body Mg 2+ balance model may help answer that question. By incorporating the present model into whole-body electrolyte balance models (e.g., [56][57][58][59]), one can obtain an integrative model to study wholebody Mg 2+ balance.…”
Section: Discussionmentioning
confidence: 99%
“…Many times, clinical trial measurements are made before the first meal in the morning, at which time sK + levels are near their lowest for the day, and therefore least likely to be above the normal range. 6,7 The model currently includes limited physiological detail (e.g., GI compartments) and limited detail on the complexity of K + regulation; this could be expanded upon in the future using information from literature based on detailed physiological experiments and data from large trials of drugs that influence K + handling (e.g., aldosterone antagonists), as explored by Stadt et al 18 and Maddah and F I G U R E 4 Model application to SZC dosing in emergency settings. Top: Flow chart of process to adjust model to simulate severe hyperkalemia to mimic desired trial population and simulate different SZC dosing regimens.…”
Section: Discussionmentioning
confidence: 99%